Utilization of Cellulose from Pineapple Leaf Fibers as Nanofiller in Polyvinyl Alcohol-Based Film - Kendri Wahyuningsih; Evi Savitri Iriani; Farah Fahma (Indonesian Journal of Chemistry, 2016)
Cellulose from pineapple leaf fibers as one of the natural polymer which has biodegradable property in a nanometer’s scale, can be formed as a filler in composite of Poly(vinyl) Alcohol/PVA is expected to increase the physical, thermal, and barrier properties of composite films similar to conventional plastic. The aim of this study was to examine the effect of fibrillation of cellulose fibers from pineapple leaf fibers using a combined technique of chemical-mechanical treatments, to investigate the reinforcing effect of concentration of nanocellulose fibrils in the polyvinyl alcohol (PVA) matrix on physical properties, thermal properties, water vapor transmission rate, light transmittance and morphological with and without addition of glycerol. Nanocellulose was made from cellulose of pineapple leaf fiber using wet milling (Ultra Fine Grinder). The composite film production was carried out by using casting solution method by mixing PVA solution with nanocellulose (10-50%) and glycerol (0-1%). The characterization of film covered physical properties (thickness, moisture content and density), thermal properties, permeability (WVTR), light transmittance, morphology, and crystallinity. Nanocellulose from pineapple leaf fibers was produced by Ultra Fine Grinder shows that the size reduction process was accurate. Nanocellulose addition on PVA composite film was affected to increasing the physical, thermal, and barrier properties. Meanwhile, decreasing the percentage of composite film transmittance, thus the transparency decrease (opaque). Water vapor transmission rate (WVTR) the film was increased with increasing glycerol concentration, but the physical and thermal properties was decreased.